2003
DOI: 10.1080/0309190021000025855
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effect on the pulse spectrum

Abstract: During the last decade, progressive achievements in haemodynamics have shown that radial artery pulse pressure can be used to estimate the vascular properties of the internal organs. Clinical experiments have shown that slow and regular respiration has a large effect on the heart rate variability (HRV). This phenomenon is called respiratory sinus arrhythmia (RSA). It is known that respiration-related oscillations in venous return cause oscillations in stroke volume and blood pressure. It also can be inferred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The rate of respiration is known to affect haemodynamics. A study in which the arterial pulse ( via heart rate and oscillometric arterial blood pressure) and peripheral resistance were analysed in healthy humans instructed to perform paced deep breathing at 20, 15, 10 and 6 breaths per min found that the rate of respiration affects the harmonics of the blood pressure pulse, which is related to the resistance of the peripheral vasculature, compliance of the aorta and hence venous return, such that slow respiration causes blood pulse fluctuations to synchronise with the heart beat rhythm [ 29 ]. Slow breathing towards a rate of 6 breaths per min has been said to result in increased venous return [ 30 ].…”
Section: Physiology Of Slow Breathingmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of respiration is known to affect haemodynamics. A study in which the arterial pulse ( via heart rate and oscillometric arterial blood pressure) and peripheral resistance were analysed in healthy humans instructed to perform paced deep breathing at 20, 15, 10 and 6 breaths per min found that the rate of respiration affects the harmonics of the blood pressure pulse, which is related to the resistance of the peripheral vasculature, compliance of the aorta and hence venous return, such that slow respiration causes blood pulse fluctuations to synchronise with the heart beat rhythm [ 29 ]. Slow breathing towards a rate of 6 breaths per min has been said to result in increased venous return [ 30 ].…”
Section: Physiology Of Slow Breathingmentioning
confidence: 99%
“…While changes in the cardiovascular system can induce changes in respiration, the influence that respiration has on the cardiovascular system is reportedly stronger [ 25 , 29 , 30 , 39 , 40 ]. Studies in healthy humans have found that controlled slow breathing, particularly at 6 breaths per min, is associated with an increase in fluctuations of both blood pressure and heart rate, compared to breathing at a typical rate [ 21 , 41 , 42 ].…”
Section: Physiology Of Slow Breathingmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood flow changes rapidly in the arteries of the extremities, especially in the peripheral arteries [26]. Changes in venous return due to respiration cause oscillations in stroke volume and blood pressure [27]. Thus, the arterial pulse should be modified by breathing [28].…”
Section: Methodsmentioning
confidence: 99%
“…The use of this system avoids operator bias, increases reproducibility, and improves accuracy. It is reported that changes in venous return due to respiration cause oscillation of the stroke volume and blood pressure (Hsieh et al, 2003). Thus, the arterial pulse should be modified by breathing (Korpas et al, 2006).…”
Section: Measurements To Compare Ra and Ba Haemodynamicsmentioning
confidence: 99%